2002
DOI: 10.1128/jcm.40.2.649-653.2002
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance of Helicobacter pylori Strains in Japanese Children

Abstract: The resistance of Helicobacter pylori to the recently available antibiotic treatment regimens has been a growing problem. We investigated the prevalence of H. pylori resistance to clarithromycin, metronidazole, and amoxicillin among 51 H. pylori isolates from Japanese children. In addition, the mutations of the corresponding gene were studied by PCR and restriction fragment length polymorphism analysis. Primary resistance to clarithromycin, metronidazole, and amoxicillin was detected in 29, 24, and 0% of strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
92
6

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(108 citation statements)
references
References 33 publications
10
92
6
Order By: Relevance
“…Despite the heterogeneity of our population (33), mutations involved in CLR r were comparable to mutations reported previously by other studies in Europe, which were mainly A2142G/43G mutations and various combinations of the wild type as well as point mutations related to the presence of multiple isolates (mixed population) in the same biopsy specimen (1,12,31,37,43,44,49). In contrast with data from many previous studies (1,2,11,24), our study identified the A2142C mutation in some strains from children, probably due to the large number of isolates in our study. The A2142C mutation was associated with a higher level of resistance (CLR MIC of Ͼ256 g/ml), with half of the strains involved being related to patients with at least 2 documented eradication failures.…”
Section: Vol 49 2011 Two-decade Survey Of H Pylori Resistance In Bcontrasting
confidence: 54%
See 1 more Smart Citation
“…Despite the heterogeneity of our population (33), mutations involved in CLR r were comparable to mutations reported previously by other studies in Europe, which were mainly A2142G/43G mutations and various combinations of the wild type as well as point mutations related to the presence of multiple isolates (mixed population) in the same biopsy specimen (1,12,31,37,43,44,49). In contrast with data from many previous studies (1,2,11,24), our study identified the A2142C mutation in some strains from children, probably due to the large number of isolates in our study. The A2142C mutation was associated with a higher level of resistance (CLR MIC of Ͼ256 g/ml), with half of the strains involved being related to patients with at least 2 documented eradication failures.…”
Section: Vol 49 2011 Two-decade Survey Of H Pylori Resistance In Bcontrasting
confidence: 54%
“…Of these strains, 9,430 were isolated from patients who were not previously treated for H. pylori infection (1,527 from children and 7,903 from adults), 1,371 strains were isolated from patients who were previously treated for H. pylori infection (162 from children and 1,209 from adults), and we have no information concerning previous eradication attempts for 24 strains.…”
Section: Resultsmentioning
confidence: 99%
“…Only a few groups have studied mutations involved in clarithromycin resistance in strains obtained from children, and their results are similar to those obtained in our study (5,13,29).…”
supporting
confidence: 80%
“…Some papers showed that A2142G was the most frequently detected (48 or 52.5%) (20,23), although some others found that A2143G was more prevalent (55.6 or 56.5%) (5,18). Only a few groups had studied the mutation involved in clarithromycin resistance in strains obtained from children; however, they found results similar to those obtained in our study (8,14,25).…”
contrasting
confidence: 53%